2003
DOI: 10.1038/sj.bjc.6601003
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive activation of STAT3 and STAT5 is present in the majority of nasopharyngeal carcinoma and correlates with better prognosis

Abstract: Constitutively activated signal transducers and activators of transcription (STAT) factors, in particular STAT1, STAT3 and STAT5, have been demonstrated in a variety of human tumours and cancer cell lines. However, data on the expression of these STATs in nasopharyngeal carcinoma (NPC) are limited. In this study, the expression patterns of STAT1, STAT3 and STAT5 were immunohistochemically examined on the archival specimens from 61 patients with NPC. Staining results of each STATs were then correlated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 30 publications
6
77
1
1
Order By: Relevance
“…In accordance to our results, Masuda et al [36] demonstrated that increased phospho-Stat3 correlated with lower disease-free survival in tongue cancer patients. Contrary results were obtained in nasopharyngeal carcinoma, where Stat3 alone could not predict prognosis but along with Stat5 predicted better disease free and overall survival [37]. Even in breast cancer, Stat3 did not have any significant predictive value for predicting outcome [38].…”
Section: Discussionmentioning
confidence: 85%
“…In accordance to our results, Masuda et al [36] demonstrated that increased phospho-Stat3 correlated with lower disease-free survival in tongue cancer patients. Contrary results were obtained in nasopharyngeal carcinoma, where Stat3 alone could not predict prognosis but along with Stat5 predicted better disease free and overall survival [37]. Even in breast cancer, Stat3 did not have any significant predictive value for predicting outcome [38].…”
Section: Discussionmentioning
confidence: 85%
“…The biomarkers include circulating markers in the blood, such as Epstein -Barr virus (EBV) DNA (Chien et al, 2001) and CYFRA 21-1 (Ma et al, 2004), as well as tumour immunohistochemical markers such as the expression of multidrug-resistance protein (Hsu et al, 2002), epidermal growth factor receptors and signal transducers and activators of transcription factors (Hsiao et al, 2003). Among them, plasma EBV DNA has been the most validated and has been shown to be a predictor of poor survival after radiotherapy for local disease (Chan et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mounting evidence from cell culture, whole animals, and patient samples indicates that Stat3 is a critical mediator of oncogenic signaling that is activated in many human malignancies (17). This evidence provides a strong rationale for developing agents that target Stat3 for treatment of cancers in which constitutive Stat3 activation plays a critical role.…”
Section: Discussionmentioning
confidence: 99%
“…2, 8 -10), is activated within cells by binding to the cell surface of Ͼ40 ligands; it also is constitutively activated in many human cancers (11)(12)(13) including 82% of prostate cancers (14), 69% of breast cancers (15), 82 to 100% of squamous cell carcinoma of head and neck (16), and 71% of nasopharyngeal carcinoma (17). Activated Stat3 upregulates the expressions of antiapoptosis proteins, such as Bcl-x L and Mcl-1, thereby decreasing spontaneous apoptosis in cancer cells (18,19).…”
Section: Introductionmentioning
confidence: 99%